Multi-cations compound Cu2CoSnS4: DFT calculating, band engineering and thermoelectric performance regulation. (June 2017) - Zhang, Dan; Yang, Junyou; Jiang, Qinghui; Zhou, Zhiwei; Li, Xin; Xin, Jiwu; Basit, Abdul; Ren, Yangyang; He, Xu
Abstract: Owing to the advantage of low thermal conductivity, large Seebeck coefficient and multiple eco-friendly components constitution, Cu2 CoSnS4 (CCTS) might be a promising thermoelectric material. DFT calculations reveal that the multiple valence bands can be utilized to obtain an enhanced Seebeck coefficient and an improved power factor, and the relatively low sound velocity in multi-cations-containing CCTS is responsible for the low thermal conductivity. Here, nano-sized CCTS sulfide has been facilely synthesized through mechanical alloying and then sintered via hot-pressing. Guided by the theoretical calculations, copper substitution is firstly adopted to regulate electrical properties and results in a highly improved power factor with an enhanced effective mass. Then, transition metal M (M = Mn, Fe, Zn) and Cu are co-doped at cobalt site to further regulate the TE performance of CCTS. As a consequence, a peak ZT value about 0.8 at 800 K is achieved in the CCTS compound simply by Cu/Mn dual-doping due to the improved electrical properties by introducing metal-like second phase and the depressed lattice thermal conductivity by weakening of covalent bonding, which is also the highest ZT value reported in 700–823 K range for metal sulfides without fast ion migration or phase transformation. Graphical abstract: The existence of multiple converged valence bands and low sound velocity are found in Cu2 CoSnS4 . Cu/M co-substitution for Cobalt is guided to improve its thermoelectric properties. Ultimately, an unprecedented high ZT of 0.8 at 800 K had been achieved due to the improved electrical properties from enhanced effective mass and the depressed lattice thermal conductivity by weakening of covalent-bonding. Highlights: The existence of multiple converged valence bands and low sound velocity are found in Cu2 CoSnS4. Single phased Cu2 CoSnS4 powders with nano size have been prepared by mechanical alloying for the first time. A highly improved power factor with an enhanced effective mass is obtained via Cu doping. An unprecedented high ZT of 0.8 at 800 K has been achieved in Cu-Mn dual doped CCTS compound.